Isolation and characterization of Pseudomonas spp. and their evaluation in management of apple replant problem - MOHINDER KAUR, SHWETA SHARMA*, I.M. SHARMA and (Indian Phytopathology, 2015)
Isolation and characterization of 30 native fluorescent Pseudomonas strains was done phenotypically (fluorescence, oxidase, catalase test, gelatin liquification, denitrification test, gelatin liquification, MR/VP, citrate utilization, arginine dihydrolysis) and genotypically (16S rRNA). They were screened for multifarious plant growth promoting activities like production of plant growth regulators, phosphate solubilization, antifungal, siderophores, HCN, ammonia and lytic enzymes. Auxins, gibberellins and cytokinins produced by isolates were in the range of 1.83-21 µg/ml, 116.1-485.8 µg/ml and 63.6-90.0 µg/ml, respectively. Pseudomonas isolates showed production of phosphate solubilizing activity in the range of 199.5 to 413.4 µg/ml available inorganic phosphate (Pi) and 67.27% SU siderophore production. Three Pseudomonas isolates (An-1-kul, An-13-kul and An-3-kul) showed maximum antifungal activities. In this study the effect of inoculation of apple rhizosphere with Pseudomonas strain was evaluated. The control treatment was uninoculated and other was inoculated with three strains of Pseudomonas spp. individually and their consortia for treatment of apple in replant field. The performance of apple seedlings was found much better in terms of plant establishment, growth promotion in terms of plant height, number of nodes and number of branches, chlorophyll content of leaves and NPK of rhizospheric soil over their respective control. These strains can be further exploited and recommended for the management of replant problem of apple.